2018
DOI: 10.2147/tcrm.s183612
|View full text |Cite
|
Sign up to set email alerts
|

Total endoscopic thyroidectomy versus conventional open thyroidectomy in thyroid cancer: a systematic review and meta-analysis

Abstract: BackgroundDespite the considerable experience gained thus far using endoscopic technologies, the role of total endoscopic thyroidectomy (ET) for papillary thyroid cancer (PTC) remains controversial. We conducted a systematic review and meta-analysis to investigate the safety and effectiveness of total ET compared with conventional open thyroidectomy (OT) in PTC.MethodsA systematic search was conducted using the PubMed, Embase and Cochrane Library electronic databases up to March 2018. The quality of included s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 48 publications
6
35
0
1
Order By: Relevance
“…16,17,34 Thus, several studies have demonstrated the superiority of scarless procedures over open surgery. 3,5,7,8,17,[29][30][31][32]34,35 However, the most certain advantage is the lack of a neck scar; the other clinical outcomes remain debatable. For example, the oncological safety of EBABA or TOETVA for patients with PTC is still unknown, and there is no worldwide consensus on this type of surgery for the treatment of this malignancy.…”
Section: From Ot To Etmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17,34 Thus, several studies have demonstrated the superiority of scarless procedures over open surgery. 3,5,7,8,17,[29][30][31][32]34,35 However, the most certain advantage is the lack of a neck scar; the other clinical outcomes remain debatable. For example, the oncological safety of EBABA or TOETVA for patients with PTC is still unknown, and there is no worldwide consensus on this type of surgery for the treatment of this malignancy.…”
Section: From Ot To Etmentioning
confidence: 99%
“…Because small PTCs, such as PTMCs, are treated by many surgeons via both endoscopic and robotic approaches, 3,7,8,19,24,27,28 many patients with larger tumors (>1.0 cm) undergo treatment with scarless surgical procedures. 16,17,19,34 Although OT is still one of the most common surgical procedures for treatment of thyroid gland pathologies, other techniques, such as ET and RT, have been gaining ground.…”
Section: Is Ptc the Most Suitable Type Of Tc For Et And Rt?mentioning
confidence: 99%
“…Despite the experience gained using such techniques in thyroid surgery, the utility in PTC remains controversial. A systematic review and meta-analysis by Chen et al (33) showed that there are limitations in endoscopic surgery due to the difficulty in obtaining views in the restricted space. Furthermore, endoscopic techniques were inferior in terms of operative time, hospital stay and transient recurrent laryngeal nerve palsy.…”
Section: Newer Surgical Techniques For Papillary Thyroid Cancermentioning
confidence: 99%
“…Furthermore, endoscopic techniques were inferior in terms of operative time, hospital stay and transient recurrent laryngeal nerve palsy. Moreover, despite similar tumour recurrence rates in the short and medium-term, the surgical completeness which may not be optimal could potentially lead to higher longer-term recurrences (33).…”
Section: Newer Surgical Techniques For Papillary Thyroid Cancermentioning
confidence: 99%
“…In 2018, thyroid cancer was the most common thyroid malignancy, accounting for ~1% of all malignant tumors, and includes papillary, follicular, undifferentiated and medullary carcinomas (1). Thyroid cancer occurs mostly in young adults aged ~40 years, and the ratio men to women is 1.0:2.5 to 1.0:3.0 (2).…”
Section: Introductionmentioning
confidence: 99%